2019
DOI: 10.2337/dc18-2432
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Prevalence by Leisure-, Transportation-, and Occupation-Based Physical Activity Among Racially/Ethnically Diverse U.S. Adults

Abstract: Leisure-time physical activity (LTPA) has been shown to prevent or delay the development of diabetes. However, little research exists examining how other domains of PA (e.g., occupation based [OPA] and transportation based [TPA]) are associated with diabetes prevalence across diverse racial/ethnic groups. We examined associations between OPA, TPA, and LTPA and diabetes prevalence and whether associations differed by race/ethnicity. RESEARCH DESIGN AND METHODS Participants in the 2011-2016 National Health and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 26 publications
(25 reference statements)
1
34
0
Order By: Relevance
“…Individuals reported details of vigorous and/or moderate intensity of PA regarding occupation‐related PA and leisure‐time‐related PA. Minutes of vigorous PA were doubled and added to minutes of moderate PA for occupation‐related PA and leisure time–related PA, as validated. ( 22 ) The total amount of PA was defined as the sum of the leisure‐time PA, occupation‐related PA, and transportation‐related PA. PA was categorized according to the 2018 PA Guidelines (adults who engage in ≥150 minutes per week of moderate‐intensity PA, 75 minutes per week of vigorous‐intensity PA, or an equivalent combination). ( 19 ) We categorized PA as “physically inactive” (“not meeting PA Guidelines ”) when individuals did not meet the criteria outlined in the 2018 PA Guidelines and as “physically active” (“meeting PA Guidelines ”) when individuals met the criteria in the 2018 PA Guidelines .…”
Section: Methodsmentioning
confidence: 99%
“…Individuals reported details of vigorous and/or moderate intensity of PA regarding occupation‐related PA and leisure‐time‐related PA. Minutes of vigorous PA were doubled and added to minutes of moderate PA for occupation‐related PA and leisure time–related PA, as validated. ( 22 ) The total amount of PA was defined as the sum of the leisure‐time PA, occupation‐related PA, and transportation‐related PA. PA was categorized according to the 2018 PA Guidelines (adults who engage in ≥150 minutes per week of moderate‐intensity PA, 75 minutes per week of vigorous‐intensity PA, or an equivalent combination). ( 19 ) We categorized PA as “physically inactive” (“not meeting PA Guidelines ”) when individuals did not meet the criteria outlined in the 2018 PA Guidelines and as “physically active” (“meeting PA Guidelines ”) when individuals met the criteria in the 2018 PA Guidelines .…”
Section: Methodsmentioning
confidence: 99%
“…This included self-reported physician-diagnosed diabetes mellitus and information regarding the use of hypoglycemic agents. For the present analysis, diabetes mellitus status was defined as an HbA1c value ≥6.5% (NGSP) or self-reported diabetes mellitus [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Inconsistent with our results, a cohort study [31] controlling the dose of physical activity suggests that VPA alone or VPA combined with MPA yield stronger health profits in terms of diabetes risk reduction compared with MPA alone. Instead of total physical activity, the cohort study includes only the effects of leisure-time exercise on diabetes risk, which may attributes to the differential effects of VPA and MPA [13]. However, engaging in vigorous physical activity up to 300 min a week attained profits in the present study, which shows higher threshold for physical activity profits compared with recommendations.…”
Section: Discussionmentioning
confidence: 66%
“…A considerable amount of research has consistently manifested that higher levels of LTPA showed apparent protective effects on the risk of diabetes compared with inactive individuals [11], and extended LTPA reduced diabetes risk furthermore [12]. In contrast, the association between physical activity with other domains and diabetes risk remains unclear [13]. The 2018 Physical Activity Guidelines for Americans recommend that older individuals perform at least 150-300 min of moderate-intensity or 75-150 min of vigorous-intensity aerobic physical activity per week in account of any domain.…”
Section: Introductionmentioning
confidence: 99%